A qualitative study of parent perspectives on barriers, facilitators and expectations for school asthma care among urban, African-American children. (3rd October 2019) - Volerman, Anna; Dennin, Margaret; Vela, Monica; Ignoffo, Stacy; Press, Valerie G.
Abstract: Objectives : Minority children experience the disproportionate burden of asthma and its consequences. Studies suggest ethnic groups may experience asthma differently with varied perceptions and expectations among parents of African-American and Latino children. Because parents coordinate asthma care with the school, where children spend a significant amount of their day, this study's goal was to determine parents' perspectives on school asthma management. Methods : Focus groups were conducted with parents of children with asthma at four urban schools whose student population is predominantly African-American. A semi-structured guide was utilized focusing on barriers, facilitators and expectations for asthma care at school. Grounded theory principles were applied in this study. Results : Twenty-two parents (91% females) representing 13 elementary and 10 middle school children with asthma (61% boys) participated in four focus groups. Most children (87%) had persistent asthma. The identified barriers to effective school-based asthma care included limited awareness of children with asthma by teachers/staff, communication issues (e.g. school/parent, within school), inadequate education and lack of management plans or systems in place. In contrast, the identified facilitators included steps that fostered education, communication and awareness, as supported by management plans and parent initiative. Parents described their expectations for increased communication and education about asthma, better systems for identifying children with asthma, and a trained asthma point person for school-based asthma care. Conclusions : Parents of children with asthma identified important barriers, facilitators and expectations that must be considered to advance school asthma management. Improved school-based asthma care could lead to better health and academic outcomes.